Macroeconomics Activity and Role of Zaka in Achieving Economic Stability (Aggregate Demand/ Mathematical Analysis Study) - Alsaad, Ahmad Mohammad; Al-Rawabdeh, Shatha Musa (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed to clarify and show the economic impact of Zaka fund development through theoretical, mathematical, and graphical analysis on macroeconomics variables which is related to aggregate demand, Researchers used theoretical, mathematical, graphical approaches for explanation economic variables. and used deductive approach through shows the effect of zakat on the aggregate Demand. The researcher concludes that the duty of Zaka induces economic growth and protects the economy from risk fluctuations whether it is recession or inflation. The researcher recommends to work on promoting the revival of Zaka, and the Zakat should be compulsory not voluntary through laws and regulations, ࢫbecause it raises the level of economic activity through its direct effect to stimulate fund investment, raise consumer’s demand and expand the market.